التهاب المهبل البكتيري بين النساء الحوامل في حضرموت-اليمن: al-Hayik, Widad M. al-Haddad, Ahmad Muhammad - al-Hayik, Widad M. al-Haddad, Ahmad Muhammad (مجلة الأندلس للعلوم التطبيقية, 2023)
Bacterial vaginosis (BV) is a common cause of abnormal or altered vaginal discharge in women of childbearing age. Its association is with obstetric and gynecologic complications. The aim of this study was to examine the prevalence of BV among pregnant women in Hadhramout-Yemen. The diagnosis of BV is usually based on clinical criteria including homogeneous vaginal discharge, an elevated vaginal pH, the presence of clue cells, and an amine odor. In this cross-sectional study we have evaluated the vaginal flora and clinical signs for 950 pregnant women. Three-hundred and seventy two (39.2%) of 950 pregnant women with abnormal vaginal discharge were positive for bacterial BV. The high rate of BV among pregnant women attending private and public obstetrics and gynecology clinics demands adequate attention to prevent BV-associated complications during pregnancy and to reduce referrals that may ensue from such complications. Our recommendation is routinely screening for BV among pregnant women to avoid infection sequelae. Adequate laboratory facilities should be provided and laboratory personnel should be trained for the diagnosis of BV.